Predicted and Back-calculated Coefficients of Permeability of Randomly Fractured Rock Mass: A Case Study - Eid, Hisham; O’Sullivan, Barry; Elshafie, Mohammed; Stollberg, Reiner; Kalin, Robert (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
This paper presents the discrepancy between the coefficients of permeability measured for randomly fractured limestone using field falling-head tests and that back-calculated for the same rock mass based on the actual discharge yielded from a dewatering system designed for a typical construction site in Doha, Qatar. The study results showed that the back-calculated coefficient of permeability is outside the range of the values measured from the falling-head tests and almost seven times higher in magnitude than the fallinghead tests average. The need of having a reliable correlation that can be used to predict the actual permeability of randomly fractured rock in terms of its rock quality indices and the results of the commonly conducted field falling-head test is highlighted.